2010
DOI: 10.1002/cbdv.200900288
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Ruthenation of Human Breast Cancer Suppressor Gene 1 (BRCA1) by the Antimetastasis Compound RAPTA‐C and Its Analogue CarboRAPTA‐C

Abstract: The interaction of two ruthenium-arene-1,3,5-triaza-7-phosphaadamantane compounds ([Ru(eta(6)-p-cymene)Cl(2)(pta)] and [Ru(eta(6)-p-cymene)(C(6)H(6)O(4))(pta)], termed RAPTA-C (3) and carboRAPTA-C (4), resp.) with the DNA sequence of the human breast-cancer suppressor gene 1 (BRCA1) has been studied using a range of techniques that probe conformation, cross-linking, base specificity, restriction analysis, and in vitro inhibition of DNA polymerization. The study demonstrates that substitution of the two labile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Platinum drugs exert their antitumor effects by binding to DNA, thereby changing the replication of DNA and inhibiting the growth of the tumor cells. For ruthenium-based drugs, there has been some evidence demonstrating an interaction between ruthenium complexes and DNAs [18,20,30]. Our previous study has demonstrated that 1 and 2 bound to the specified DNA fragment of the human breast cancer suppressor gene 1 (BRCA1) through the intercalative mode into the base pairs of DNA, and the DNA-binding constants (K b ) for 1 and 2 were 7.09 × 10 4 M -1 and 5.19 × 10 5 M -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum drugs exert their antitumor effects by binding to DNA, thereby changing the replication of DNA and inhibiting the growth of the tumor cells. For ruthenium-based drugs, there has been some evidence demonstrating an interaction between ruthenium complexes and DNAs [18,20,30]. Our previous study has demonstrated that 1 and 2 bound to the specified DNA fragment of the human breast cancer suppressor gene 1 (BRCA1) through the intercalative mode into the base pairs of DNA, and the DNA-binding constants (K b ) for 1 and 2 were 7.09 × 10 4 M -1 and 5.19 × 10 5 M -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the cisplatin-resistant cell line this preference is reduced and shifted towards the nucleus and cytosol [98]. A c c e p t e d M a n u s c r i p t 65 The nature of interactions of RAPTA-C and carbo-RAPTA-C ( Figure 19, (49)) with the DNA sequence of the human breast cancer suppressor gene 1 (BRCA1) was investigated using conformational analysis of ruthenated DNA, crosslinking assays and semi-quantitative PCR [104]. In accordance with the results described above ruthenation induced unwinding of the supercoiled DNA.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…The calculation also revealed that the arene ring of 2 does not interfere with WatsonCrick base-pairing of adjacent bases nor intercalate between basepairs, which is different from [(h 6 -p-cymene)Ru(en)Cl] þ . Since these simulations suggest 2 forms DNA adducts akin to that of cisplatin, a study into the nature of ruthenated DNA lesion was undertaken using conformational analysis of ruthenated DNA, interstrand crosslinks assays and semi-quantitative PCR [51]. Restriction analysis indicated that 2 preferentially binds at purine sites and that the lesions are capable to inhibiting DNA polymerization.…”
Section: Reactivity Towards Dna and Other Biomoleculesmentioning
confidence: 99%